Synthesis, characterisation and thermal behaviour of solid state compounds of 4-methylbenzylidenepyruvate with heavier trivalent lanthanides and yttrium(III) - Marques, R. N. [UNESP]; Melios, C. B. [UNESP]; Ionashiro, Massao [UNESP] (Elsevier B.V., 2003)
Solid state Ln-4-Me-BP compounds, where Ln stands for heavier trivalent lanthanides (gadolinium to lutetium) and yttrium(III) and 4-Me-BP is 4-methylbenzylidenepyruvate (CH3-C6H4-CH=CH-COCOO-), have been synthesized. Elemental analysis, complexometry, X-ray powder diffractometry, infrared spectroscopy and simultaneous thermogravimetry-differential thermal analysis (TG-DTA), have been used to characterise and to study the thermal behaviour of these compounds. The results provided information concerning the stoichiometry, crystallinity, ligand's denticity, thermal stability and thermal decomposition. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: 4-Methylbenzylidenepyruvate; Characterization; Complexes; Heavier trivalent lanthanides; Thermal behaviour; Yttrium(III); 4 methylbenzylidenepyruvate; Lanthanide; Pyruvic acid derivative; Unclassified drug; Yttrium; Complex formation; Differential scanning calorimetry; Solid state; Synthesis; Thermal analysis; Thermogravimetry; Thermostability; X ray powder diffraction